Rehabilitation of a Bauxite Tailing Substrate in Central Amazonia: The Effect of Litter and Seed Addition on Flood-Prone Forest Restoration - Dias, André T.C.; Bozelli, Reinaldo L.; Darigo, Ricardo M.; Esteves, Francisco de A.; dos Santos, Heraldo F.; Figueiredo-Barros, Marcos P.; Nunes, Maria Fernanda Q. S.; Roland, Fabio; Zamith, Luiz R.; Scarano, Fabio R. (Restoration ecology, 2012)
Impacts of mining activity can be particularly difficult to remediate in wetland ecosystems subject to inundation pulses due to the reduced length of the plant growing season. We used a factorial experiment to test whether litter and seed addition could be used to increase the efficiency of ecological restoration on a flood‐prone forest (known as igapó) impacted by deposition of bauxite tailings. Our results clearly showed that the addition of litter collected from pristine igapó areas increased plant growth, seedling density, and seedling species richness. The increase in individual plant growth was echoed at the community level with higher leaf area index values on litter addition plots compared to controls. Litter addition can enhance reaccumulation of nutrient pools during successional development, which has been proposed as an important feature to ensure self‐sustainability of areas under restoration. The success of the seed addition treatment depended on the species used. Of the seven sown species, only Acosmium nitens (a leguminous nitrogen‐fixing species) showed high establishment. The introduction of nitrogen‐fixing species is also expected to build up the nitrogen pool in the system as has been reported for restoration programs in non‐inundated forests. These practices have the advantage, compared to direct fertilizing, of not causing eutrophication of water bodies when applied to flood‐prone vegetation.